Reorientation of Mentawai Youth in Fighting for the Local Religion of the Arat Sabulungan Traditional Community of the Mentawai Tribe - Jamaldi,; Pismawenzi,; Akmal, Dinul (Islam Transformatif : Journal of Islamic Studies, 2024)
The recognition of religion and Freedom of Religion or Belief (FoRB) for the Mentawai people is urgent in safeguarding their human rights to practice their faith. One of the key advocates for religious rights is the Mentawai youth. This article focuses on the reorientation of Mentawai youth in advocating for the recognition and FoRB of the Arat Sabulungan local religion, an indigenous belief system of the Mentawai Tribe in Indonesia. The rights of followers of Arat Sabulungan, particularly religious recognition, FoRB, and the inclusion of religion in identity documents, have been subject to discrimination and prohibition in the Mentawai community to this day. This study identifies several motivations and orientations among the youth advocating for religious freedom and belief, including the preservation of Mentawai culture, the pursuit of religious freedom, and the general recognition of the rights of the Mentawai people.